Experimental tests of a 263 GHz gyrotron for spectroscopic applications and diagnostics of various media - Glyavin, M. Yu; Chirkov, A. V.; Denisov, G. G.; Fokin, A. P.; Kholoptsev, V. V.; Kuftin, A. N.; Luchinin, A. G.; Golubyatnikov, G. Yu; Malygin, V. I.; Morozkin, M. V.; Manuilov, V. N.; Proyavin, M. D.; et al. (Review of scientific instruments, 2015)
A 263 GHz continuous-wave (CW) gyrotron was developed at the IAP RAS for future applications as a microwave power source in Dynamic Nuclear Polarization / Nuclear magnetic resonance (DNP/NMR) spectrometers. A new experimental facility with a computerized control was built to test this and subsequent gyrotrons. We obtained the maximum CW power up to 1 kW in the 15 kV/0.4 A operation regime. The power about 10 W, which is sufficient for many spectroscopic applications, was realized in the low current 14 kV/0.02 A regime. The possibility of frequency tuning by variation of the coolant temperature about 4 MHz/1 °C was demonstrated. The spectral width of the gyrotron radiation was about 10−6.